Effects of the evolving global tobacco product landscape on smokers' switching behaviors - Stokłosa, Michał Jerzy (School of Economics, 2020)
How effectively governments can use tobacco tax as a public health and a revenue-generating measure depends on how able smokers are to circumvent the tax by switching to other tobacco products. Recently, tobacco product switching has become more common, especially with many new tobacco product types appearing on the market. The research on these switching behaviors is scarce. This thesis provides analysis in three aspects tobacco product switching: (1) price-driven between-product substitution, (2) switching to newly-introduced tobacco products and (3) switching to products on which no domestic tax has been paid. When the ratio of tobacco product prices changes, consumers sometimes choose to switch between products. Zambia, with a high prevalence of roll-your-own (RYO) tobacco, a less costly alternative to factory-made (FM) cigarettes, is a case in point. The study presented in the second chapter of this thesis used individual-level data obtained from the 2012 and 2014 waves of the ITC Zambia Survey to model the probability of FM and RYO cigarette smoking, as well as between-product substitution. It found that increasing the cigarette tax, with corresponding price increases, could significantly reduce cigarette use in Zambia. Furthermore, reducing between-product price differences would reduce substitution from FM to RYO. With the proliferation of many new tobacco product types, traditional cigarettes are becoming less dominant. With the introduction of a new product to the market, between-product switching might not be influenced purely by price differences across product types, but rather driven by the increased variety of products on the market. Chapter three makes use of a natural experiment created during the rollout of a heated tobacco product, IQOS, in 2015 and 2016 in Japan to examine if trends in cigarette sales have changed with the introduction of IQOS in each region. A series of placebo models are estimated to test if events other than IQOS introduction could have better explained trends in cigarette sales. The results show that the introduction of IQOS likely reduced cigarette sales in Japan. Large differences in cigarette prices observed between geographical regions might incentivize some smokers from regions with higher cigarette prices to switch to cheaper cigarettes available across the border. The fourth chapter uses 2004-2017 official European Commission data and a methodology developed by Becker (1990), to analyze the association between prices and crossborder cigarette purchases in the European Union. Incentives for cross-border purchasing are measured as a function of differences in cigarette prices between bordering countries, controlling for population density near borders and for gasoline prices. The scale of cross-border cigarette purchasing in the EU is small, and not-significant through maritime borders. An upward convergence of cigarette prices across EU Member States would further reduce the cross-border purchasing problem.